Pengaruh kompetensi sumber daya manusia dan pemanfaatan teknologi informasi terhadap kualitas laporan keuangan bumdes di wilayah Kecamatan Karangrejo - Khoirunisa, Nanda Anggi; Khoiriawati, Novi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of human resource competence and the use of information technology on the quality of BUMDes financial reports on 13 BUMDes in Karangrejo District. The method used in this research is quantitative with the type of associative research. The sampling technique used is saturated sampling or census, with a total sample of 39 respondents. Data analysis in this study used data instrument tests (validity test and reliability test), classical assumption test (normality test, multicollinearity test, and heteroscedasticity test) and hypothesis testing (coefficient of determination test, F test and T test) using the SPSS version. 25 for windows. The results of this study indicate that partially the variable of human resource competence has a significant positive effect on the quality of BUMDes financial reports and the use of information technology variables does not have a positive effect on the quality of BUMDes financial reports. Meanwhile, simultaneously, the variables of human resource competence and the use of information technology have a significant positive effect on the quality of BUMDes' financial reports